Trypanosoma cruzi Exploits Wnt Signaling Pathway to Promote Its Intracellular Replication in Macrophages - Volpini, Ximena; Ambrosio, Laura F.; Fozzatti, Laura; Insfran, Constanza; Stempin, Cinthia C.; Cervi, Laura; Motran, Claudia Cristina (Frontiers in Immunology, 2018)
During the acute phase of Trypanosoma cruzi infection, macrophages can act as host cells for the parasites as well as effector cells in the early anti-parasitic immune response. Thus, the targeting of specific signaling pathways could modulate macrophages response to restrict parasite replication and instruct an appropriate adaptive response. Recently, it has become apparent that Wnt signaling pathway exerts immunomodulatory functions during inflammation and infection. Here, we tested the hypothesis that during T. cruzi infection, the activation of Wnt signaling pathway in macrophages plays a role in modulating the inflammatory/tolerogenic response and therefore regulating the control of parasite replication. In this report, we show that early after T. cruzi infection of bone marrow derived macrophages (BMM), β-catenin was activated and Wnt3a, Wnt5a, and some Frizzed receptors as well as target genes of Wnt/-catenin pathway were up-regulated, with Wnt proteins signaling sustaining the activation of Wnt/β-catenin pathway and then activating the Wnt/Ca+2 pathway. Wnt signaling pathway activation was critical to sustain the parasite’s replication in BMM; since the treatments with specific inhibitors of β-catenin transcriptional activation or Wnt proteins secretion limited the parasite replication. Mechanistically, inhibition of Wnt signaling pathway armed BMM to fight against T. cruzi by inducing the production of pro-inflammatory cytokines and IDO activity and by down-regulating arginase activity. Likewise, in vivo pharmacological inhibition of the Wnts’ interaction with its receptors controlled the parasite replication and improved the survival of lethally infected mice. It is well established that T. cruzi infection activates a plethora of signaling pathways that ultimately regulate immune mediators to determine the modulation of a defined set of effector functions in macrophages. In the present study, we have revealed a new signaling pathway that is activated by the interaction between protozoan parasites and host innate immunity, establishing a new conceptual framework for the development of new therapies.